A case of treatment-resistant bipolar depression and comorbid OCD treated with deep brain stimulation of the medial forebrain bundle: 5 years follow-up results. (July 2021) - Oldani, Lucio; Benatti, Beatrice; Macellaro, Monica; Porta, Mauro; Servello, Domenico; Zekaj, Edvin; Dell'Osso, Bernardo
Highlights: Deep brain stimulation shows efficacy in treatment resistant bipolar depression. The medial forebrain bundle is a promising target for deep brain stimulation. Deep brain stimulation reduces obsessive compulsive symptoms. Deep brain stimulation exerts a mood stabilizing activity. Deep brain stimulation shows fast and durable clinical improvement. Abstract: Limited though promising evidence exists on the efficacy of Deep Brain Stimulation (DBS) of the Medial Forebrain Bundle (MFB) in otherwise intractable patients with Major Depression and Obsessive-Compulsive Disorder (OCD). Herein, we present acute and follow-up results (up to 5 years) of a 42 year old man with a diagnosis of treatment-resistant Bipolar Depression (BD) and comorbid OCD, successfully treated with DBS of the MFB. Regular follow-up visits with psychometric evaluations highlighted a considerable improvement of patient's depressive and OC symptoms at 5 years from implant. According to the limited, reported experience, we support the efficacy and tolerability of DBS of the MFB as a promising intervention in patients with treatment-resistant BD and comorbid OCD, with specific emphasis on the long-term outcome.